2005
DOI: 10.1063/1.2131184
|View full text |Cite
|
Sign up to set email alerts
|

Trapped torsional vibrations in elastic plates

Abstract: Abstract-We have observed that torsional vibrations can be trapped in elastic plates with circular regions of slightly thicker steps or with smooth convex contoured surfaces. An electromagnetic acoustic transducer (EMAT) was used to generate oscillatory surface traction. The resonant frequencies and Q-values were measured. It was found that these trapped torsional modes have Q-values exceeding 100,000 with pure inplane motion, which is of practical importance for acoustic sensor applications.In this paper, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The uncoupling of torsional modes from flexural modes allows pure in-plane motion of the resonator, which is advantageous for applications requiring immersion in or in contact with liquids [12]. It is evident from Eq.…”
Section: Two-dimensional Plate Equationsmentioning
confidence: 87%
See 2 more Smart Citations
“…The uncoupling of torsional modes from flexural modes allows pure in-plane motion of the resonator, which is advantageous for applications requiring immersion in or in contact with liquids [12]. It is evident from Eq.…”
Section: Two-dimensional Plate Equationsmentioning
confidence: 87%
“…The theoretical results from this study were compared to experimental measurements [12,23]. Circular steps and contoured regions were machined in a 6000 series cast aluminum plate.…”
Section: B First-order Torsional Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such plates are of interest because torsional vibrations may be trapped near the steps, similar to that in stepped solid cylinders [11] and trapping of thickness-shear vibrations in contoured plates [17]- [19]. Recent experiments by Knowles et al [26] have observed trapped torsional modes in both stepped and contoured aluminum plates, which may be used to design sensors with improved performance in the presence of liquids. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, no compressional waves are generated in the adjacent liquid, and the sensor response can be related to the liquid properties without concerning the liquid thickness. Previously we have demonstrated that energy-trapping torsional-mode vibrations can be excited in elastic plates by using an electromagnetic acoustic transducer (EMAT) [10,11]. In this paper, experiments are conducted to study effect of liquid thickness on the torsional-mode resonators, in comparison with thickness-shear mode.…”
Section: Introductionmentioning
confidence: 99%